VOLTAIRE’S PHILOSOPHY: HUMAN NATURE AND INTERPRETATION OF RELIGION - Yu. Zimaryova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the article is to determine and reconsider Voltaire’s ideas concerning religion and human nature. In order to achieve this purpose it is necessary to complete the following tasks: to analyse academic literature on Voltaire’s interpretation of the phenomenon of religion; to expose Voltaire’s basic ideas about human nature; to substantiate the importance of anthropological approach to the phenomenon of religion with the ideas of Voltaire’s philosophical works. Methodology. The achievements of anthropocentric philosophical thought of the XIX century possess great potential in the process of constructive comprehension and theoretical reconstruction of the anthropological intention that accompanies the process of philosophising. The research extensively applies hermeneutical method for interpreting Voltaire’s philosophy. Scientific novelty. In academic literature on Voltaire’s works we have ascertained the basic anthropological component of his philosophy and reconsider Voltaire’s ideas about religion as something that is rooted in human nature. Conclusions. In academic literature the interpretation of the phenomenon of religion in Voltaire’s heritage is a rather controversial one. At the one hand, Voltaire criticizes religion for its superstitions and fanaticism. On the other hand, he recognises the existence of God. In our opinion, the phenomenon of religion should be examined in the context of human nature and basic problems related to it such as the problem of soul and the problem of free will. The anthropological approach to the phenomenon of religion allows to avoid the extremity of atheistic and metaphysical approaches and to enable its anthropological interpretation.